Pérez Calle, Begoña (2023). Flora Tristán. Economic thought and social communication in times of Romanticism. Madrid: Dykinson, p. 181 (ISBN: 9788411709217; eISBN: 978-84-1170-921-7; Collection: Contemporary Knowledge, no. 164) - Sánchez-Bayón, Antonio (Iberian Journal of the History of Economic Thought, 2024)